Household debt and consumption during the financial crisis: Evidence from Danish micro data - Asger Lau Andersen; Charlotte Duus; Thais Lærkholm Jensen (Danmarks Nationalbank, 2014)
We use data for nearly 800,000 Danish families to examine whether high household leverage prior to the financial crisis may have amplified the reduction in household spending over the course of the crisis. We find a strong negative correlation between pre-crisis leverage and the change in non-housing consumption during the crisis, conditional on a range of other household characteristics. The larger drop in spending among the highly leveraged families reflects that these families consumed a larger fraction of their income than their less-leveraged peers prior to the crisis. But as the crisis unfolded, this difference in consumption levels between high- and low leverage families vanished. Moreover, we find suggestive evidence that the drop in consumption for the highly leveraged families cannot be fully explained by a contraction in credit supply.
Keywords: D12; E21; E65; 330; household debt; financial crises; micro data